Capacity for Preferences and Pediatric Assent: Implications for Pediatric Practice - Navin, Mark Christopher (The Hastings Center report, 2019)
In the past thirty to forty years, clinicians and bioethicists have expanded the scope for children’s participation in decision-making about their medical care, often under the banner of “pediatric assent.” The success of this movement was signaled perhaps most strongly by the creation of American Academy of Pediatrics guidance on pediatric assent in 1995. We agree with the AAP that both the best interests of the child patient and the need to respect the child patient are reasons to take seriously children’s treatment preferences. However, we argue that the AAP could provide a stronger and more stable ethical foundation for pediatric assent. Current policy documents invoke a conception of respect that is grounded in autonomy and cannot apply in most cases of pediatric assent. We argue that the mere fact that children have treatment preferences is a reason to support pediatric assent. We defend this claim by focusing on the importance of what we have called “capacity for preferences.” The notion of capacity for preferences underscores that the moral value of a patient’s preferences is not reducible to considerations of either autonomy or best interests.